CHALLENGES OF MEDICAL CARE OF PHYSICAL DISABLED PATIENTS IN ANÁPOLIS MUNICIPALITY (CIPEEX, 2022)
DEFICIENCY IS ANY LOSS OR ABNORMALITY OF A STRUCTURE, AND / OR PSYCHOLOGICAL, PHYSIOLOGICAL OR ANATOMICAL FUNCTION THAT GENERATES INCAPACITY FOR THE PERFORMANCE OF ACTIVITY, WITHIN THE STANDARD CONSIDERED NORMAL FOR THE HUMAN BEING. ACCORDING TO THE WHO, IN 2011, IT IS CURRENTLY ESTIMATED THAT 15% OF THE WORLD POPULATION HAS SOME DEFICIENCY. THE PROMOTION AND SUPPORT OF THE INCLUSION OF DISABILITY ISSUES STILL DEPEND ON INDIVIDUAL INITIATIVES, RATHER THAN A POLICY OF MEDICAL SCHOOLS THAT COULD ENSURE THEIR CONTINUITY. IN 2002, IT WAS PROPOSED TO INTRODUCE REHABILITATION CONTENTS AND HEALTH CARE FOR PEOPLE WITH DISABILITIES IN UNDERGRADUATE HEALTH CURRICULA, BUT IT IS STILL SOMETHING THAT IS NOT SEEN. LACK OF ACCESSIBILITY OR RESOURCE CONSTRAINTS AFFECT PEOPLE WITH DISABILITIES, AS IT IMPAIRS FREE ACCESS TO HEALTH EQUIPMENT AND DIRECTLY EXCLUDES THEIR FULL RIGHTS AS CITIZENS AND HUMAN BEINGS. A CROSS-SECTIONAL, QUANTITATIVE AND COMPARATIVE STUDY WILL BE CARRIED OUT THROUGH THE APPLICATION OF A QUESTIONNAIRE TO PHYSICIANS FROM THE BASIC HEALTH UNITS AND THE PRIVATE HOSPITALS OF THE CITY OF ANÁPOLIS IN ORDER TO IDENTIFY THE CHALLENGES FOR A GOOD CARE OF THE DISABLED PATIENTS, AS WELL AS VERIFY THE CHARACTERISTICS OF THE PHYSICAL SPACE THAT INFLUENCES THE CARE OF THE PHYSICALLY HANDICAPPED PATIENT AND COMPARE THE DIFFICULTIES FOUND IN PUBLIC AND PRIVATE INSTITUTIONS. IT IS OBSERVED THAT THE DIFFICULTIES FACED BY PHYSICALLY HANDICAPPED INDIVIDUALS, EVIDENT IN OTHER STUDIES, SUGGEST PROBLEMS RANGING FROM THE ESTABLISHMENT OF PHYSICIAN-PATIENT COMMUNICATION, TO THE STRUCTURAL LIMITATIONS FOR ACCESS TO CARE IN THE UNITS.
Keywords: Medical care. Limitations. Disabled people.